Instructional competence, commitment, job satisfaction, research and extension services of two categories of master's graduates in physical education - Bellosillo, Neomi Marabut (1997)
The objective of this study was to determine whether significant differences exist in the level of instructional competence, commitment to job and to organization, job satisfaction and involvement in research work and extension/community services of the two groups of master's graduates in Physical Education, Master of Science in Physical Education (MSPE) and Master of Physical Education (MPE). Participation in research work and in community/extension services are significantly affected by the variables: salary, bachelors degree, and civil status. The variables: supervisory and administrative position, sex, master's degree and other factors only affect participation in research work while university graduated from, age and other unidentified factors affect the latter.
Computer print-out (photocopy)
Thesis (Ph.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Physical education and training -- Study and teaching; Physical education teachers -- Job satisfaction. -- Philippines; Teachers -- Training of